PENGARUH ARUS KAS OPERASI DAN STRUKTUR MODAL TERHADAP PERTUMBUHAN LABA (Studi Empiris pada Perusahaan Subsektor Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2021 - Sriyani, Nani; Wizanasari, Wizanasari; Fitrianti, Dini (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This study aims to determine how the influence of Operating Cash Flow and Capital Structure on Profit Grow. This type of research uses associative quantitative, the object of research is banking sub sector companies listed on the Indonesia Stock Exchange in 2018- 2021, using purposive sampling method in collecting data. sample data and the type of data used is secondary data. The totalpopulation in this study were 44 companies and the total sample used in this studywas 40 of 10 companies for a period of 4 years. Analysis of the data used in this study using panel data regression using the Eviews 12 Software. The results of this study indicate that simultaneously the variables Operating Cash Flow and Capital Structure affect Profit Grow. Based on the results of the T hypothesis test,it shows that Operating Cash Flow has an effect on Profit Grow, and Capital Structure has no effect on Profit Grow.